(untitled) (Bangladesh Heart Journal, 2024)
Background: Although rare, cardiac myxomas are the most common primary cardiac tumor with an incidence of 0.5 per million per year. Clinical presentation is variable and ranges from intracardiac obstruction, embolization to the pulmonary and systemic circulation, heart failure or constitutional symptoms. Surgical resection is the only effective treatment to prevent its debilitating and catastrophic complication. Case summary: Here, three atypical presentations as well as three different locations of cardiac myxomas were reported. First one is a rare case of ST-elevated myocardial infarction due to myxoma that originated from the left ventricle. One case involved right sided myxomas with pulmonary embolism. The third case involved huge left atrial myxoma combined with recurrent syncope. All three cases were almost misdiagnosed due to their atypical presentation. Echocardiography was the primary tool for detecting and diagnosing these cases. Subsequently all three patients underwent successful resection of myxoma. We also review clinical presentations and diagnostic characteristics of cardiac myxomas. Conclusion: Rare cardiac myxomas may have various clinical and imaging features. Physicians especially other non-cardiologist must increase their awareness of this disease and engage in the early diagnosis. Echocardiography is the diagnostic procedure of choice. The long-term survival after surgical resection is excellent and recurrence is rare. Bangladesh Heart Journal 2024; 39(1): 63-68